E-021 Safety and efficacy of a low dose eptifibatide infusion during endovascular treatment of tandem occlusions. (23rd July 2017) - Roels, C; Brown, M; Janjua, R; Heck, D
Abstract : Background: Tandem occlusion of the cervical internal carotid artery and the internal carotid artery terminus or middle cerebral artery represents a special, and more challenging, type of emergent large vessel occlusion. Unlike the more straightforward case of cardiogenic embolism, the tandem occlusion presents the simultaneous problem of an intracranial embolus, and an acute thrombotic event in the cervical carotid artery. Tandem occlusions challenge the neurointerventionalist to balance the competing priorities of preventing intracranial hemorrhage with establishing and preserving patency of the cervical internal carotid artery. The optimal medical regimen to achieve the best outcomes has not been defined. Methods: We describe our experience with 23 consecutive cases of extracranial carotid stent placement and intracranial embolectomy using a low dose eptifibatide protocol consisting of a 135 mcg/kg bolus followed by a 0.5 mcg/kg/min infusion for up to 36 hours. Patients were converted to oral therapy (aspirin and a 300–600 mg loading dose of clopidogrel) after confirmation of absence of hemorrhage on CT 12–24 hours post procedure. Data were extracted by retrospective review of a prospective database. Results: Demographics are given in the table. All 23 patients had CT within 12–24 hours post procedure. 20 received ultrasound of the carotid artery between 24 and 36 hours post procedure (2 were deceased prior to ultrasound), and 16 had follow up ultrasound at 30–90 days. Clinical follow up at 90 days was 100% (14 in person, 3 by chart review, 6 deceased) with MRS determined by a practitioner certified in the NIHSS and MRS. Technical success was 87% (TICI 2B/3). In one case the infusion was begun but stopped immediately after a recognized guidewire perforation in the middle cerebral. That patient died of a large ischemic stroke. There was one case of fatal hemorrhagic stroke conversion after stenting and embolectomy (5%). Of the 20 patients receiving ultrasound the following day, 2/20 (10%) had asymptomatic stent occlusion. Of the 14 additional patients receiving ultrasound between 30 and 90 days, there were another 2 asymptomatic occlusions (bringing the total to 4 of 16, 25%). At 90 days there were 6 deaths (26%) and 10/23 (43%) were independent. Conclusions: The low dose eptifibatide infusion resulted in a low incidence of SICH (5%) in the endovascular treatment of tandem intracranial occlusions. The infusion was not potent enough to maintain patency of the carotid artery in all patients. However, re-occlusion of the carotid artery was asymptomatic in the 4 patients where it occurred. This underscores that extracranial re-occlusion of the carotid artery is the lesser of evils compared with hemorrhagic stroke conversion. Limitations of the study include retrospective data collection, a low incidence of intravenous t-PA use, and lack of independent adjudication of angiographic and clinical outcomes. Disclosures: C. Roels: None. M. Brown: None. R. Janjua: None. D. Heck: 2; C; Stryker.